2017
DOI: 10.18632/oncotarget.23628
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan attenuates pressure-overload- or post-infarction-induced cardiac remodeling in mice

Abstract: Either angiotensin converting enzyme inhibitor (ACEI) or angiotensin receptor 1 blocker (ARB) attenuates cardiac remodeling. However, the overall molecular modulation of the reversing remodeling process in response to the ACEI or ARB treatment is not yet well determined. In this study, we examined whether gene expressions are modulated by ACEI (temocapril), ARB (olmesartan) or both in a murine model with transverse aortic constriction (TAC) and confirm whether periostin is a target gene of olmesartan in mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Animal experiments revealed that ACEIs or ARBs protect heart from injury by multiple mechanisms under pressure overload or ischemia. In addition to the upregulation of ACE2 level, these drugs promote the proliferation of endothelial progenitor cells (EPCs), increased periostin expression or blocking TGF-β signaling in heart tissue after myocardial infarction or pressure overload (22)(23)(24)(25). Whether ACEIs/ARBs reduces cardiac troponin release or protect cardiac injury in hypertension patients with COVID-19 merits a large population of study.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments revealed that ACEIs or ARBs protect heart from injury by multiple mechanisms under pressure overload or ischemia. In addition to the upregulation of ACE2 level, these drugs promote the proliferation of endothelial progenitor cells (EPCs), increased periostin expression or blocking TGF-β signaling in heart tissue after myocardial infarction or pressure overload (22)(23)(24)(25). Whether ACEIs/ARBs reduces cardiac troponin release or protect cardiac injury in hypertension patients with COVID-19 merits a large population of study.…”
Section: Discussionmentioning
confidence: 99%